Activated‐Carbon Nanofibers/Graphene Nanocomposites and Their Adsorption Performance Towards Carbon Dioxide. Issue 10 (12th August 2020) - Othman, Faten Ermala Che; Yusof, Norhaniza; Ismail, Ahmad Fauzi
Abstract: Activated‐carbon nanofibers (ACNFs) provide a relatively new, modified structure of carbon‐based adsorbents that have the ability to adsorb carbon dioxide due to their high specific surface area, wide distribution of porous structures, and high volume of active sites. In this study, cost‐effective agricultural waste‐based graphene synthesized from rice husk ashes was used as additive to enhance the ACNF properties. ACNF/graphene (gACNF) is still a relatively unexplored adsorbent. The resultant gACNF exhibited better thermal stability properties, with higher yield, larger specific surface area, and higher micropore volume. These properties are the main factors contributing to their enhanced adsorption performance towards CO2 . Abstract : An activated‐carbon nanofibers/graphene nanocomposite was developed as adsorbent material with enhanced porous structure and high adsorption performance towards carbon dioxide. The graphene‐based material used was synthesized from graphene‐derived rice husk ashes, an abundant and cheap agricultural waste, providing an alternative for realizing green technology.